Maktab direktorlarining taym-menejment diagnostikasi: hozirgi holatni tahlil qilish va takomillashtirish yoʻllari (SCIENCE and SOCIETY, 2025)
The article analyzes the results of diagnostics of principals of secondary schools on the effective use of working and personal time. The tasks, methods, goals of diagnosing time management, issues of the manager’s working time and its effective use are covered.